Pedro A. Barceló. Roms auswärtige Beziehungen unter der Constantinischen Dynastie (306-363), Verlag Friedrich Pustet, Regensburg, 1981, 226 pp. ISBN: 3-791 7-0735-3. - Sanz, Rosa (Gerión. Revista de Historia Antigua, 1985)
Sin resumen